2014
DOI: 10.1111/jopr.12162
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of the Cytotoxicity and Water Sorption of Two Different Denture Base Systems

Abstract: The tested denture base materials adhered to the ISO standards for both cytotoxicity and water sorption. The cytotoxicity of the light-activated UDMA resin tested was statistically similar to that of the heat-activated PMMA resin; however, the UDMA resin exhibited decreased water sorption in long-term water storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…Our results were in correlation with the results obtained by Akin et al 8 who also reported similar findings in their study. They assessed the water sorption and cytotoxicity of UDMA and PMMA resins denture base systems.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…Our results were in correlation with the results obtained by Akin et al 8 who also reported similar findings in their study. They assessed the water sorption and cytotoxicity of UDMA and PMMA resins denture base systems.…”
supporting
confidence: 83%
“…8 For obtaining the wax patterns, a stainless steel mold was used, which measured 1 mm 3 in dimension. For packing of the PMMA and UDMA resins, placements of the wax patterns of the test specimens in the dental stone were done.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of unreacted methacrylate monomer in denture base resins is undesired because it impedes the resin’s mechanical properties [7] and also compromises the product’s biocompatibility. Unfortunately, a certain amount of residual monomer is inevitable due to the monomer-polymer equilibrium necessary for free radical polymerisation of denture base resins [8], and the desired zero residual monomer cannot be achieved [8].…”
Section: Introductionmentioning
confidence: 99%